HUBUNGAN PENYESUAIAN DAN PENANGANAN PSIKOLOGIS DALAM KONTEKS KURIKULUM MERDEKA PADA GENERASI Z (STUDI PADA SISWA KELAS X TSM SMK NEGERI 1 REJOTANGAN) - Aldi Bayu Saputra; Rico Andhika Putra; Riza Dwi Ahmadi (Journal of Automotive Vocational Education (JAVED), 2025)
ABSTRACT Aldi. 2025. The Relationship Between Adjustment and Psychological Coping in the Context of the Independent Curriculum Among Generation Z (A Study on 10th Grade TSM Students at SMK Negeri 1 Rejotangan). Undergraduate Thesis, Vocational Automotive Technology Education Study Program, Faculty of Science and Technology, Universitas Bhinneka PGRI. Advisor: Rico Andhika Putra, M.Pd. Keywords: Psychological Adjustment, Psychological Coping Strategies, Learning Effectiveness, Independent Curriculum, Generation Z. The transformation of the education system through the Independent Curriculum has had a significant impact on the learning patterns of vocational high school students, especially 10th graders who belong to Generation Z—known for being adaptive yet psychologically vulnerable. Challenges such as academic pressure, environmental adjustment, and the need for emotional management strategies have become crucial factors to consider. This study aims to determine the relationship between psychological adjustment and psychological coping strategies with the effectiveness of the Independent Curriculum learning among 10th grade TSM students at SMK Negeri 1 Rejotangan. This research employed a quantitative correlational method, with data collected through questionnaires. The respondents consisted of 85 students selected using simple random sampling. Data analysis was conducted using validity and reliability tests, classical assumption tests, and Pearson correlation with the assistance of SPSS software. The results showed that psychological adjustment had a very weak and insignificant relationship with learning effectiveness, with r = -0.031 and significance 0.776 ( 0.05). Psychological coping strategies also showed a very weak and insignificant relationship, with r = -0.062 and significance 0.573 ( 0.05). Simultaneously, both variables did not show a significant relationship with learning effectiveness. These findings indicate that although students’ psychological factors are important, they are not the main determinants of success in implementing the Independent Curriculum. External factors such as teachers’ approaches, learning environment, and teaching methods tend to have a more dominant influence on perceptions of learning effectiveness.